Anti-feminist Movement, Hegemonic Patriarchy, and Gender Equality Challenges: The Case of the Sexual Violence Elimination Bill - Laila Kholid Alfirdaus; Lupyta Agra Divina; Fitriyah Fitriyah (Jurnal Humaniora, 2022)
Challenges to gender equality in Indonesia are not only related to men and male patriarchy. Using the case of the Sexual Violence Elimination Bill, women, specifically those supported by the party affiliated with political Islam, can also hamper the promotion of women’s rights and equality. Hegemonic patriarchy explains the phenomenon through relating the rejection against the Bill to the patriarchal tendencies planted through religious institutions and teaching. The teaching that places women as a secondary creature after men and as the object of men’s authority (Imamah), is taken for granted, believed to be transcendental, turned into an ideology, and concretized through a movement against feminism. All points that try to assert women’s fundamental rights in the Bill are coined as Western values and are rejected as seen as anti-Islam. Reflecting from the case, it becomes clear that challenges towards gender equality are currently getting harder, as they come not only from patriarchal men, but also women who are hegemonized by patriarchal values and take an anti-feminist stance as part of preserving Islam. Tracing through secondary and primary sources, applying desk reviews and interviews with male and female activists, both for and against the Bill, this paper identifies that the rise of anti-feminist sentiment is rooted alongside contemporary Islamization, which has mushroomed in the post-Reformasi era, and poses new challenges to promoting gender equality.